Food safety importance of biophosphate applications in safe food crop productions - Someus Edward; Palotai Zoltán; Hantosi Zsolt; Bordós Gábor (WESSLING Nemzetközi Kutató és Oktató Központ Közhasznú Nonprofit Kft. Budapest, 2016)
Disrupted nutrient recycling is a problem for Europe and all over the world. Phosphorus and nitrogen, instead of being used for plant nutrition, are lost across environmental media during food production or are wasted. Regarding phosphate fertilisers, the European Union (EU) is currently highly dependent on import of phosphate rock mined outside of the EU. There is no any possibility to substitute Phosphorus in agricultural food crop and animal productions. Therefore, phosphorous recovery and recycling is one of the key priorities of sustainable agricultural systems in the EU and worldwide as well. The “3R” Recycle-Reduce-Reuse zero emission pyrolysis technology and carbon refinery is specifically designed for the high added value recycling and recovery of BIO-PHOSPHATE, BIO-NPK-C nutrients and bio-materials with different carbon structures, which refined carbon and mineral products can safely be applied in the organic/low input agriculture and adsorber industries. Animal Bone bioChar “ABC” is a recovered organic phosphorus fertiliser, made from food grade animal bone grist, having high nutrient density (30% P2O5) and pure Pcontent. The rendering industrial origin food grade category 3 animal bone grist processed ABC is a macro-porous organic fertilizer with as high as 92% pure calcium phosphate and only 8% carbon content. ABC in all agricultural application cases is BIO-NPK-C formulation optimised, enhancing of soil microbiological life, having high water holding and macromolecular organic nutrient retention. The fully safe ABC is used at low doses (100–600 kg/ha) and in cases when justified even up to 1,000 kg/ha. Therefore the ABC product functionalities are organic fertilizer, soil improver, growing medium and/or fertilising product blend. The substitution of phosphate import by recovered phosphorus is an important goal for the European agriculture already in short term, for which 3R technology processed ABC has over 20% continuous substitution potential in the EU28 before 2030.
Keywords: Műszaki és technológiai tudományok; Egyéb műszaki tudományok és technológiák; Élelmiszer és italfélék